(untitled) (The Strategic Review for Southern Africa, 2020)
Published for the past 35 years, this journal has witnessed major social and political changes in Southern Africa, the wider African continent and the rest of the world. The Strategic Review for Southern Africa has responded to these shifts by aligning its analyses to capture the challenges facing Southern Africa within an increasingly interlinked and dynamic world. The rationale and context of such adjustments to new realities were assessed in the introductory essay to the last issue (No 1 of 2013), which also presented the ’new face’ of this periodical. We shall, of course, maintain continuity by engaging with analyses of socio-political, economic and geostrategic developments that impact on or provide lessons for Southern Africa. This understanding includes a wider concept of the region and the continual yet varying impact on Southern Africa from elsewhere. We thus welcomed the offer by two renowned scholars from the Nordic countries to act as guest editors of the thematic focus in this issue: the effects of the so-called Arab spring on French speaking Central and West Africa, in particular Mali and Mauritania of the Sahel region. Also, South Africa’s military engagement in other parts of the continent has demonstrated that the inter-connectivity of societies and regions has reached new dimensions. As one of the most influential and powerful member states of the African Union, South Africa has resumed responsibility as a continental actor far beyond the Southern African sub-region. It is hence of direct relevance and importance what happens elsewhere on the continent in terms of transitions and conflicts.